68Ga Extemporaneous Preparations in Radiopharmacy - Marzia Rizzello; Anna Pacelli; Maria Domenica De Bari; Annalisa Cutrignelli; Rosa Maria Iacobazzi; Antonio Lopalco; Nunzio Denora (Pharmaceutics, 2025)
Gallium-68 (68Ga) radiopharmaceuticals are increasingly used in nuclear medicine due to their rapid production capabilities and exceptional specificity in molecular imaging applications. Several of these tracers have demonstrated remarkable clinical efficacy across various oncological conditions, including prostate cancer, neuro-endocrine tumours, and cancers expressing fibroblast activation protein. Commercial kits allow the use of the standardised production protocol, but extemporaneous preparations are the economic and flexible alternatives, particularly within hospital-based radiopharmacy settings. However, such preparations need meticulous conformity to quality control measures and regulation to ensure safety and effectiveness. This review provides an analysis of current methodologies employed in 68Ga extemporaneous preparations and examines pertinent regulatory frameworks. Further clinical validation trials and technical advancement remain essential to facilitate the routine clinical practice’s widespread usage and long-term feasibility of such preparations.